The Analysis of Junior High School Teacher-Made Tests for the Students in Enrekang - Husni A (Faculty of Education and Teacher Training of IAIN Palopo, 2020)
The research aimed at finding out information about the preparation of constructing teacher-made tests in Enrekang, the quality of English teacher-made test according to item analysis, and the level cognitive domain of the teacher-made test. The test quality was determined after it was used in school examination test. This research employed survey research using descriptive method. The researcher analyzed the data and then described the research finding quantitatively. The population of this research was the teachers who teach in ninth grade at junior high schools in Enrekang. This research applied simple random sampling technique by taking four different schools as sampel. The results of analysis show preparation that junior high school teachers follow in constructing teacher-made tests in Enrekang is divided into five main parts. In preparing the test, the procedures were considering tests’ materials and proportion of each topic, choosing to check the item bank that match to syllabus and indicators, or preparing test specification. In writing test, teachers’ procedures were re-writing chosen test item from internet and textbook, re-writing items that was used before and allowing the other teachers to verify it, combining items from item bank and text book, or making new item. While in analyzing a test, the procedures used by the teachers were analyzing and revising test based on its item difficulty, predicting the item difficulty and revising the test, or doing nothing to analyze the test. About the timing in preparing the test, there are three out of five teachers who need only one week to construct multiple choice tests. Besides, there are two out of five teachers who need two weeks to construct multiple choice tests. While the teachers have different ways in providing test based on students’ ability. Moreover, the item analysis shows that no test is perfectly good. It was found that almost all tests need to be revised. It was also found that there were only three categories works in all tests based on the cognitive domain of the test namely knowledge, comprehension, and application categories. There was no item belong to analysis, synthesis, and evaluation categories.